Phylogenomic analysis of Tibouchina s.s. (Melastomataceae) highlights the evolutionary complexity of Neotropical savannas - Jantzen, Johanna R. (2022)
The origin of the high biodiversity in the Neotropics remains an unresolved but critical question, especially for the species-rich but understudied savannas of Brazil, such as the campos rupestres and Cerrado. To address this knowledge gap, we leveraged Tibouchina s.s., a clade of flowering plants in Melastomataceae found in the Cerrado and campos rupestres, to uncover the processes that generated the hyper-diverse flora of Neotropical savannas. We used a phylogenomic approach combined with ecological niche modelling and biogeographic analysis to infer the evolutionary processes that have influenced the diversification of Tibouchina s.s. We identified the importance of multiple interacting evolutionary forces, including geographical and ecological divergence, polyploidy and hybridization, and found that Tibouchina s.s. harbours greater diversity than once thought due to polyphyletic species, polyploid species and previously undocumented species. Taken together, these findings support a complex evolutionary history for Tibouchina and underscore the need for continued efforts to generate thoroughly sampled, robust phylogenetic trees for additional plant clades of these threatened Neotropical savannas and for intensive collecting and taxonomic work in these highly diverse but neglected regions.